GC-MS analysis and antibacterial activity of some fractions from Lagochilus ilicifolius Bge. grown in Mongolia - Dumaa, M.; Gerelt-Od, Ya.; Javzan, S.; Otgonhkishig, D.; Doncheva, Ts.; Yordanova, G.; Philipov, S.; Selenge, D. (Mongolian Journal of Chemistry, 2016)
3-methyl-1,2,3,4-tetrahydroquinoline (1), 4-hydroxyisoquinoline (2), 4-(1E)-hydroxy-1-prophenyl)-2-methoxyphenol (3), 4-acetoxycinnamic acid (4), Songoramine (5), and Songorine (6) have been determined by GC-MS analysis from the crude alkaloid mixtures (G1) obtained from the aerial parts of Lagochilus ilicifolius Bge. grown in Mongolia and comparison of the measured data with those from the literature. The compounds 1-6 are described for the first time from L.ilicifolius. From these 3-methyl-1,2,3,4-tetrahydroquinoline (1) was determined for the first time from natural plants. In addition, the antibacterial activity of fractions and total alkaloids were evaluated against Staphylococcus aurous, Bacillus subtilis, Bacillus cereus and Escherichia coli strains, respectively. The growth inhibition zones against gram-positive S.aureus, B.subtilis, B.cereus and gram negative E.coli, strains were observed. Positive results were achieved on 500 μg/disc concentration, but lower results or no active on 100 μg/disc concentration were for the plant extracts, fractions and total alkaloids. Mongolian Journal of Chemistry 16 (42), 2015, 39-43